Case Study: Observation of Dysmenorrhea Pain Removal with Hypnotherapy Method - R.A. Helda Puspitasari; Erik Kusuma; Ayu Dewi Nastiti; Dwining Handayani (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Hypnotherapy is a method of planting suggestions when the brain is in a relaxed state, but that does not mean falling asleep or being unconscious during practice. Hypnotherapy can also be said as a thought therapy and healing technique that uses the hypnotic method to give positive suggestions or commands to the subconscious mind for healing a psychological disorder or to change thoughts, feelings, and behaviors for the better. This case study was conducted on first grade students of Diploma 3 Nursing Study Program, Faculty of Nursing, Jember University. After obtaining permission to conduct a case study, the observer identified respondents with inclusion criteria, gave informed consent. Next, collect primary data, primary data includes observations of pain scales, anxiety scales, fatigue scales, patterns of sports activities. The inclusion criteria that will be used are first grade, do not experience menstrual pattern disorders, experience primary dysmenorrhea on the first day, and are willing to be respondents The sample in this case study consists of 2 students, college student I and college student A. Age, education and exercise patterns have an effect on the pain felt during dysmenorrhea. Factors associated with dysmenorrhea are pain scale, anxiety scale and fatigue scale, where both patients showed a correlation between pain felt with anxiety and fatigue experienced when dealing with dysmenorrhea.